2022
DOI: 10.3390/electronics11152317
|View full text |Cite
|
Sign up to set email alerts
|

Google Mobility Data as a Predictor for Tourism in Romania during the COVID-19 Pandemic—A Structural Equation Modeling Approach for Big Data

Abstract: Our exploratory research focuses on the possible relations between tourism and the mobility of people, using short longitudinal data for mobility dimensions during the COVID-19 pandemic. One of these is real-time, exhaustive type data, published by Google, about the mobility of people in six different dimensions, (retail, parks, residential, workplace, grocery, and transit). The aim is to analyze the directional, intensity, causal, and complex interplay between the statistical data of tourism and mobility data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Measures taken by authorities to restrict travel during the Covid-19 pandemic had beneficial effects on promoting domestic tourism, online/virtual tourism activities, and the use of environmental aspects such as air quality to create attractiveness and competitiveness in the tourist destination market. Nagy et al, 2022, Nagy et al, 2023 Industrial development in rural areas indirectly leads to a medium to long-term decrease in the number of tourists in those areas.…”
Section: Rodrigues Et Al 2021mentioning
confidence: 99%
“…Measures taken by authorities to restrict travel during the Covid-19 pandemic had beneficial effects on promoting domestic tourism, online/virtual tourism activities, and the use of environmental aspects such as air quality to create attractiveness and competitiveness in the tourist destination market. Nagy et al, 2022, Nagy et al, 2023 Industrial development in rural areas indirectly leads to a medium to long-term decrease in the number of tourists in those areas.…”
Section: Rodrigues Et Al 2021mentioning
confidence: 99%
“…Two of three elements were considerable affected by COVID-19 pandemic but the ITC gain, after pandemic time, in importance (Rahman, 2023). During the COVID pandemic and ever since, we have a large-scale open database about the movement and real motion of people in different types of urban and nonurban areas around the world (Nagy et al, 2022; as Google Mobility data and Apple Mobility data, no study of shown how many movements may affect a country's overall competitiveness and this aspect justified to take into consideration the mobility data reported during a particular time, respectively the COVID-19 pandemic. So, we intend to measure if the Google and Apple mobility indices cand predict (or not) the movement of TTCI during pandemic compared with pre-pandemic TTCI ranks.…”
Section: Introductionmentioning
confidence: 99%
“…There are also preoccupations regarding the solutions and innovation in tourism industry after Covid-19 pandemic in countries with important seasonal tourism in total economy as Montenegro (Ratković et al, 2022) especially to find certain models of implementation of innovative solutions, which could affect the more dynamic development of tourism (Ratković et al, 2022). Tourism has developed rapidly, in the age of consumerism due to the special interest of tourists for more concentrated activities or tourist experiences based on interests (Agarwal, 2018), due to the mobility of people in urban areas or between cities (Nagy, Gabor & Bacoș, 2022) and recently based on Google Mobility or Apple Mobility data available online, for almost any location in the world, at city, county, or country level the tourists preferences and/or predicted visited place can be modeled (Nagy, Gabor & Bacoș, 2022). The Romanian tourism, as emerging market and destination for tourism worldwide, as an economic-social activity, through a good management of the tourism destination, can have an important contribution to GDP, because it benefits from a rich and varied natural, anthropical and historical heritage.…”
Section: Introductionmentioning
confidence: 99%
“…• Using of electronic application for different smart phones like Google Maps and/or Apple to forecast and follow the movement of people to find models and predict the tourism data (Nagy, Gabor & Bacoș, 2022).…”
Section: Introductionmentioning
confidence: 99%